Sustainability Analysis of the Revolving Fund Program of the LPDB (Revolving Fund Management Institution): MICMAC Method Approach - Fino Rihab Dibihantoro; Ni Nyoman Reni Suasih (Universitas Muhammadiyah Ponorogo, 2024)
The importance of access to credit for micro, small, and household craft enterprises, including cooperatives, has become a major focus in improving working capital financing and capital accumulation to support industrial income. The government through the LPDB (Revolving Fund Management Institution) has launched a revolving fund program that aims to strengthen the capital base of cooperatives, increase the capacity of human resources in business and financial management, and increase the role of cooperatives in expanding employment opportunities and reducing poverty. According to data from the Cooperative Business Development Division of the Denpasar City MSME Cooperative Office, from 2021 to 2023, there were five cooperatives that received the LPDB revolving fund program, but did not consistently reapply for the funds. This raises concerns regarding the sustainability of the program and the factors that influence it. This study aims to identify the factors that influence the sustainability of the LPDB program for cooperatives in Denpasar City. Using the MICMAC (Matrix of Cross Impact Multiplications Applied to a Classification) analysis method, this study reveals that the revolving fund administration requirements and members' information and knowledge about the revolving fund have the most significant direct influence. These findings underscore the importance of simplifying the administrative process and improving member knowledge to ensure the success of the program. In addition, active member participation emerged as an important predictor of program sustainability, highlighting the importance of members' direct involvement in supporting their economic activities. Thus using this method can uncover critical factors, and provide a comprehensive understanding that can inform policy adjustments and strategic implementation to improve program sustainability.